Franciszek Karpiński and Marcin Poczobut: On the Correspondence Between the Rector of Vilnius Academy and the Poet-Landowner - Chachulski, Tomasz (Senoji Lietuvos literatūra, 2021)
Marcin Poczobut, the rector of Vilnius Academy, and the poet Franciszek Karpiński exchanged at least a few letters between 1787 and 1799. Their correspondence was accompanied by poetry written by Poczobut, who was an amateur poet, and by Karpiński, a poet well known and respected. The biographies of both authors are discernible in the background of their correspondence. Karpiński had just settled in the Grand Duchy of Lithuania and, after leasing several villages, bought one of his own; he gained new acquaintances and friends. For Poczobut, it was an opportunity to come to know the poet, to engage him into the circle of the staff of Vilnius Academy, to establish a friendship and learn the poet’s opinion on his own literary works. Despite several attempts, they failed to establish closer cooperation, and only these letters remain as an evidence of their contacts.